2011
DOI: 10.1007/s11357-011-9250-4
|View full text |Cite
|
Sign up to set email alerts
|

Compression leggings modestly affect cardiovascular but not cerebrovascular responses to heat and orthostatic stress in young and older adults

Abstract: We tested the hypothesis that wearing commercially available compression leggings would attenuate postural reductions in mean arterial blood pressure (MAP) and cerebral perfusion during heat stress, particularly in older adults. Six older (70 years±4) and six younger (29 years±4) males were heated (esophageal temperature raised 0.5°C) in a water-perfused suit whilst wearing compression or control leggings (>1 week apart, randomized order). Blood flow velocity in the middle cerebral artery (MCAv), blood pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 45 publications
3
23
0
Order By: Relevance
“…This may allow CS to have a greater net effect on blood volume and pooling in the lower extremities. A similar hypothesis has been proposed by Lucas et al after examining the effect of compression leggings on young and elderly individuals subjected to combined heat and orthostatic stress. The authors found that under combined heat and orthostatic stress, compression leggings maintained MAP by passively reducing the venous pooling in the lower limbs and increasing TPR.…”
Section: Discussionsupporting
confidence: 71%
“…This may allow CS to have a greater net effect on blood volume and pooling in the lower extremities. A similar hypothesis has been proposed by Lucas et al after examining the effect of compression leggings on young and elderly individuals subjected to combined heat and orthostatic stress. The authors found that under combined heat and orthostatic stress, compression leggings maintained MAP by passively reducing the venous pooling in the lower limbs and increasing TPR.…”
Section: Discussionsupporting
confidence: 71%
“…This raises an interesting question: What is limiting the increase in cardiac output in aged adults during heat stress, despite an augmentation of cardiac function? In this study, the attenuated increase in cardiac output was primarily driven by an attenuated increase in heart rate, consistent with similar observations for this age group (12,14,21,22). Increases in heart rate during heat stress occur mainly through changes in cardiac parasympathetic/sympathetic neural activity and to a lesser extent because of the direct effect of temperature on the heart (13,17).…”
Section: Discussionsupporting
confidence: 90%
“…Nonetheless, aged adults are unable to maintain stroke volume during heat exposure (25,26). Importantly, this inability to maintain stroke volume fully accounts for the attenuated increase in cardiac output, as heart rate responses are generallythough not always (12,14,21,22)-similar to the young (23,25,26). These results suggest that although Doppler-derived indexes of systolic function are augmented during heat stress in aged adults (23), cardiac contractility may not increase sufficiently to maintain stroke volume during heat-induced reductions in cardiac filling pressures.…”
Section: New and Noteworthymentioning
confidence: 99%
“…It was shown that, in addition to marked lowering of cerebral perfusion (as indexed by MCAv) with ageing, there are further age-related reductions in MCAv and slower corrections of MAP with resuming the upright posture in both normothermic and passive heat conditions (269); however, these changes were otherwise asymptomatic to represent a physiologically acceptable insult, at least with mild elevations (0.5 • C rise in esophageal temperature) in body temperature. The utility of compression garments to attenuate postural reductions in mean arterial blood pressure and cerebral perfusion during heat stress during supine rest and orthostasis was minimal with a +0.5 • C increase in esophageal temperature (268).…”
Section: Aging Thermoregulation and Cerebrovascular Functionmentioning
confidence: 98%
“…In fact, only two studies to date have examined such interactions in both young (29 ± 4 years) and otherwise healthy elderly participants (70 ± 4 years) (268,269). It was shown that, in addition to marked lowering of cerebral perfusion (as indexed by MCAv) with ageing, there are further age-related reductions in MCAv and slower corrections of MAP with resuming the upright posture in both normothermic and passive heat conditions (269); however, these changes were otherwise asymptomatic to represent a physiologically acceptable insult, at least with mild elevations (0.5 • C rise in esophageal temperature) in body temperature.…”
Section: Aging Thermoregulation and Cerebrovascular Functionmentioning
confidence: 99%